Serum hyaluronic acid and procollagen III, N-terminal propeptide levels are highly associated with disease severity and predict the progression of COVID-19 - Yang, Ti; Liu, Le Le; Wu, Xin Han; Xue, Jian Guo; He, Chun Yan (Frontiers in Cellular and Infection Microbiology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic is a rapidly evolving global emergency and continuously poses a serious threat to public health, highlighting the urgent need of identifying biomarkers for disease severity and progression. In order to early identify severe and critical patients, we retrospectively analyze the clinical characteristics and risk indicators of severe disease in patients with corona virus disease 2019 (COVID-19).: A total of 420 confirmed COVID-19 patients were included in the study. According to the "Diagnosis and Treatment of novel coronavirus Pneumonia (10th Edition)", the cases were divided into mild group (n = 246) and severe group (n =147). Laboratory parameters were analyzed in combination with clinical data. Results: Male patients over 46 years who have smoking habits were more likely to suffer from severe COVID-19. Critically ill patients had lower lymphocyte counts and red blood cell counts, and higher white blood cell counts (P<0.05). Expectedly, serum inflammatory factors (NLR, PLR, LMR, CLR, PCT, CRP), coagulation markers (APTT, PT, TT, FIB, D-Dimer), Myocardial damage markers (hs-TNT, LDH) were significantly increased (P<0.05) in severe COVID-19 patients. Surprisedly, those patients showed obviously elevated levels of common tumor markers (ProGRP, CYFRA21-1, SCC, NSE) (P<0.05). In this case, the levels of tumor marker reflected more the condition of inflammation than the growth of tumor. More importantly, HA and PIIIN-P were highly associated with COVID-19 severity. The AUC of the ROC curve for the diagnosis of severe COVID-19 by HA and PIIIN-P was 0.826. Meanwhile, HA was positively correlated with myocardial damage markers (hs-TNT, LDH). PIIIN-P was positively correlated with myocardial damage markers (hs-TNT, LDH) and inflammatory factors (NLR, PLR, LMR, CLR, ProGRP, SCC, PCT, CRP). On the contrary, PIIIN-P was negatively correlated with pulmonary function indexes (oxygenation index and oxygen saturation of hemoglobin).HA and PⅢN-P are highly associated with disease severity and progression of COVID-19 and can be used as new markers for the prediction of severe COVID-19.